Addition of crude glycerin to pig diets: sow and litter performance, and metabolic and feed intake regulating hormones. (23rd December 2015) - Hernández, F.; Orengo, J.; Villodre, C.; Martínez, S.; López, M.J.; Madrid, J.
Abstract : The continued growth in biofuel production has led to a search for alternative value-added applications of its main by-product, crude glycerin. The surplus glycerin production and a higher cost of feedstuffs have increased the emphasis on evaluating its nutritive value for animal feeding. The aim of this research was to evaluate the effect of the dietary addition of crude glycerin on sow and litter performance, and to determine the serum concentrations of hormones related to energy metabolism and feed intake in sows during gestation and lactation. A total of 63 sows were assigned randomly to one of three dietary treatments, containing 0, 3 or 6% crude glycerin (G0, G3 and G6, respectively) added to a barley-soybean meal-based diet. During gestation, none of the dietary treatments had an effect on performance, while during lactation, glycerin-fed sows consumed less feed than those fed the control diet (3.8 v . 4.2kg DM/day; P =0.007). Although lactating sows fed the G3 diet had a higher BW loss than those fed the control diet (−20.6 v. −8.7 kg; P =0.002), this difference was not reflected in litter performance. In gestation, the inclusion of glycerin did not affect blood concentrations of insulin or cortisol. However, pregnant sows fed diets supplemented with glycerin showed lower concentrations of acyl-ghrelin and higher concentrations of leptin (−55 and +68%, respectively; P <0.001). In lactating sows, there were no differences between dietary treatments for any of the hormones measured. Pre-prandial acyl-ghrelin concentrations were positively correlated with cortisol concentrations during gestation ( r= 0.81; P =0.001) and lactation ( r= 0.61; P= 0.015). In conclusion, the inclusion of up to 6% crude glycerin did not affect the performance of sows during the gestation period; however it had a negative effect on the feed intake and weight loss of lactating sows. Moreover, further research is needed to elucidate the potential relationship between glycerin inclusion levels in the diet and the serum concentrations of hormones related to feed intake and energy balance control.